2021
DOI: 10.1002/mgg3.1711
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of fragile X syndrome carrier screening during prenatal diagnosis: A pilot study at a single center

Abstract: Background Fragile X syndrome (FXS) is the most common inherited form of intellectual disability. Prenatal screening of FXS allows for early identification and intervention. The present study explored the feasibility of FXS carrier screening during prenatal diagnosis for those who were not offered screening early in pregnancy or prior to conception. Methods Pregnant women to be offered amniotic fluid testing were recruited for the free voluntary carrier screening at a single center between August, 2017 and Sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Because the presence of a PM can lead to developmental disability in future generations, carrier screening has important reproductive and mental health implications for the woman who has to be tested, and it is relevant for early detection, intervention, and family planning. A recent study investigating the feasibility of fragile X carrier screening for pregnant women and for the fetuses during prenatal diagnosis reported that, over a total of 7000 pregnant women, approximately 61% of them consented to receive carrier screening [ 471 ]. The study identified five PM carriers and three women with a full mutation, and suggested that implementation of carrier screening during prenatal diagnosis may provide information about early intervention for those who have the FMR1 mutation, and information on the risk of having a child with FXS in the following pregnancies.…”
Section: Screening For Fragile X and Fxpacmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the presence of a PM can lead to developmental disability in future generations, carrier screening has important reproductive and mental health implications for the woman who has to be tested, and it is relevant for early detection, intervention, and family planning. A recent study investigating the feasibility of fragile X carrier screening for pregnant women and for the fetuses during prenatal diagnosis reported that, over a total of 7000 pregnant women, approximately 61% of them consented to receive carrier screening [ 471 ]. The study identified five PM carriers and three women with a full mutation, and suggested that implementation of carrier screening during prenatal diagnosis may provide information about early intervention for those who have the FMR1 mutation, and information on the risk of having a child with FXS in the following pregnancies.…”
Section: Screening For Fragile X and Fxpacmentioning
confidence: 99%
“…Importantly, the identification of women carriers of a PM who are at risk for FXPOI could lead to more effective reproductive interventions for those who want to have a child. In addition, it has been reported that prenatal screening is beneficial when considering the burden of raising a child with FXS [ 471 ].…”
Section: Screening For Fragile X and Fxpacmentioning
confidence: 99%